Factors Associated with Maternal Behavior in Complementary Feeding Practices among Mothers of Children aged 6–24 months - Athanasia Astuti; Sri Mulyanti (Utan Kayu Publishing, 2026)
This issue is important to address because appropriate complementary feeding (MP-ASI) plays a crucial role in supporting child growth and development as well as preventing stunting. Maternal behavior in complementary feeding practices significantly determines the quality of nutritional intake during the child’s critical growth period. However, complementary feeding practices are still influenced by various factors, including cognitive and sociodemographic aspects. Therefore, it is important to examine whether these factors are associated with maternal behavior within the context of primary health care services. This study aimed to analyze the relationship between maternal characteristics—namely knowledge, attitude, age, education, and occupation—and complementary feeding practices among children aged 6–24 monthsin the working area of Gambirsari Public Health Center, Surakarta. This study used a quantitative approach with a cross-sectional design. The study subjects consisted of mothers with children aged 6–24 months. The sample was selected using a purposive sampling technique. The variables examined included independent variables (maternal knowledge, attitude, age, education, and occupation) and the dependent variable (complementary feeding behavior). Data were collected using a structured questionnaire covering respondent characteristics, knowledge, attitudes, and feeding practices. Data analysis was performed using the Fisher’s Exact test with a 95% significance level (α = 0.05). A total of 34 mothers participated in the study. Most respondents demonstrated good complementary feeding behavior (94.1%), while all respondents had good knowledge (100%). No statistically significant association was observed between maternal attitude (p=0.595), age (p=0.437), education (p=0.795), occupation (p=0.792), and complementary feeding behavior. Knowledge could not be analyzed because all respondents were classified in the same category. Based on the findings of this study, continuous efforts are recommended to improve the quality of education and support provided to mothers regarding complementary feeding practices. Such efforts should not only focus on enhancing maternal knowledge but also take into account other factors beyond individual characteristics that may influence feeding behaviors. Furthermore, future studies are encouraged to explore additional factors that were not examined in the present study, such as family support, cultural influences, and access to health information.